Rosencrantz and Guildenstern are dead - Stoppard, Tom
Alvin Theatre, David Merrick, by arrangement with The National Theatre of Great Britain, presents "Rosencrantz and Guildenstern are Dead," by Tom Stoppard, directed by Derek Goldby, associate director Claude Chagrin, scenery and costumes by Desmond Heeley, lighting by Richard Pilbrow, music by Marc Wilkinson, associate producer Samuel Liff, with Brian Murray, John Wood, Paul Hecht, Alexander Courtney, Noel Craig, B.J. DeSimone, Ralph Drischell, Roger Hamilton, Michael Holmes, Carl Jocobs, Roger Kemp, Dino Laudicina, Roy Lozano, Patricia McAneny, Anne Meacham, Douglas Norwick.